Complaint management system using SMS database : case study : Republic Indonesia General Consulate, Johor - Rakhmadi, Akmal (2008)
inbox unpub unspecified FSKSM 2008-00 completed 160 Universiti Teknologi Malaysia, Faculty of Computer Science and Information System Faculty of Computer Science and Information System masters thesis